Occurrence and characterisation of calcium oxalate crystals in stems and fruits of Hylocereus costaricensis and Selenicereus megalanthus (Cactaceae: Hylocereeae). (October 2016) - Viñas, María; Jiménez, Víctor M.
Highlights: Calcium oxalate crystals are present in Hylocereus costaricensis and Selenicereus megalanthus . At least five crystal forms were observed in tissues analyzed. Mono- and dihydrated forms were (simultaneously) found. Highest crystal contents were measured in greenhouse stems, followed by fruit peels. Analyzed pulp was devoid of crystals. Abstract: Detailed description about occurrence of calcium oxalate (CaOx) crystals in the edible vine cactus species Hylocereus costaricensis and Selenicereus megalanthus is scarce. Therefore, we evaluated and characterized the presence, morphology and composition of CaOx crystals in both species. Crystals were isolated from greenhouse and in vitro vegetative stems, and from ripe fruit peels and pulp by enzymatic digestion and density centrifugation and quantified with a haemocytometer. Morphologies were studied using scanning electron microscopy, elemental composition with energy-dispersive X-ray spectroscopy and salt composition with X-ray powder diffraction. Analyses conducted confirmed that isolated crystals were exclusively composed by CaOx, both mono- and dihydrated. Highest crystal contents were measured in greenhouse stems, followed by the fruit peels. While very few crystals were quantified in in vitro plants, they were not detected in the fruit pulp at all, which is of advantage for its human consumption and could be linked to mechanisms of seed dispersal through animals. Different crystal morphologies were observed, sometimes varying between genotypes and tissues analysed. This is the first work known to the authors with a detailed characterization of CaOx crystals in vine cacti.